DEVELOPMENT OF STUDENT WORKSHEETS BASED ON PEER LED TEAM LEARNING MODEL ON COLLOIDAL MATERIAL - Zulfadli Zulfadli; Isyqa Silma; Habibati Habibati; Kana Puspita; Latifah Hanum; Rahmad Rizki Fazli (Lantanida Journal, 2023)
To further improve achievement of the given learning objectives, chemistry learning requires instructional materials that encourage active engagement of students. The goal of this research was to create student worksheets based on Peer Led Team Learning (PLTL) on colloid material, to establish the validity of student worksheets based on PLTL on colloid material, and assess teacher and student responses to worksheets. PLTL based students on colloid material that has been developed. This research approach is known as research and development (R&D), and it is carried out utilizing the 4D model (define, design, develop, and disseminate). Purposive sampling was used for the sample technique. The study was carried out at four schools: MAN 3, SMAN 5, SMAN 12, and SMAN 15 Adidarma Banda Aceh. Validating the practicality of student worksheets and questionnaire responses from teachers and students were used to obtain data. This study obtained the following results: (1) validation of the feasibility of student worksheets by expert validators of 92.3% and based on the chemistry teacher's assessment of 86.5% in the very good or valid category; (2) results of the teacher's responses to the students' worksheets obtained a percentage of 88.1% in the very good category; and (3) results of the students'responses to the students' worksheets obtained a percentage of 79.9% in the good category. Based on the findings, it is possible to infer that the student worksheet based on PLTL on colloid material is appropriate for use as teaching material on colloid material.